PENGARUH CURRENT RATIO DAN DEBT RATIO TERHADAP RETURN ON ASSET PADA PT.TIMAH BANGKA (PERSERO) TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2019 - Febransyah Febransyah; Herlan Junaidi; Septo Wijaya (Universitas Tridinanti, 2022)
This study aims to analyze the effect of Current Ratio and Debt Ratio on Return On Assets at PT Timah Tbk. The samples used in this study were 36 samples. Multiple linear regression analysis method. on the variables and through the SPSS for Windows 26.00 program. The regression coefficient for the Current ratio variable is 0.778 which states that each addition of 1% CR will cause an increase in the ROA value of 0.778 and for the Debt Ratio variable of -2.437, it states that each addition of 1% DR will cause a decrease in the ROA value of 2.437. the coefficient of determination (R2) is 0.908 or 90.8% meaning that the combination of independent variables, namely X1 (Current Ratio), X2 (Debt Ratio) is able to explain the dependent variable (Y) namely ROA of 90.8%, the rest is 9.2% (100% - 90.8% ) is explained by other variables not examined in this study. Partial test results (t) for the Current Ratio, the results of the comparison between tcount and ttable are 1.613 < 2.035 and Sig value is 0.116 > 0.05. This shows that the Current Ratio does not have a significant partial effect on Return On Assets. and the results of the partial test calculation for the Debt Ratio, the results of the comparison of tcount and ttable are [-9.922] > 2.035 and the value of Sig 0.00 < 0.05. The results of the regression coefficient test can be concluded that the Debt ratio has an effect on Return On Assets. Simultaneous test results (F) can be seen that the calculated F value is 162,303 with a significance value of 0.000. This indicates that the calculated F value has a value greater than Ftable (162,303 > 3.28) and the sig value is 0.00 < 0.05. The results of the regression coefficient test can be concluded that the Current Ratio and Debt Ratio simultaneously have a positive and significant effect on Return On Assets. For further research, researchers suggest using other independent variables such as Acid Test Ratio, Return on investment, receivable turnover, Total Asset turnover, debt to equity ratio that can affect Return On Assets that has not been studied in this studKeywords: Current Ratio, Debt Ratio and Return On Asset